Texturing method and solar cell

By forming an oxide glass layer containing P-type doping elements on the pyramid suede of crystalline silicon solar cells and finely processing, the bottom angle and side inclination of the pyramid structure are increased, and the controllability of the pyramid structure in the prior art is solved. The problem of insufficient has significantly improved the light utilization rate and reduced the reflectance.

CN119486320APending Publication Date: 2025-02-18JA SOLAR TECH YANGZHOU
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411648272.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing velvet making method has limited control over the pyramid structure, resulting in little improvement in light utilization. Multiple velvet making may lead to corrosion of the tower spiral and reduce light utilization.

Method used

The pyramid suede is prepared on the surface of the crystalline silicon matrix, and an oxide glass layer containing P-type doping elements is formed on the suede, and a partial oxide glass layer at the tower body and bottom of the tower is removed, the spiral part is retained, and further production is carried out Fleece treatment to increase the bottom angle and side inclination of the pyramid structure.

Benefits of technology

By increasing the controllability and light trapping properties of the pyramid structure, the light utilization rate of crystalline silicon solar cells is significantly improved and the reflectance is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119486320A_ABST
    Figure CN119486320A_ABST
Patent Text Reader

Abstract

The invention discloses a texturing method and a solar cell. The texturing method comprises the following steps: preparing a pyramid textured surface on the surface of a crystalline silicon substrate; forming an oxidized glass layer on the pyramid suede; removing the parts, corresponding to the pyramid suede, of the tower body and the tower bottom in the oxidized glass layer, and reserving the part, corresponding to the tower tip, in the oxidized glass layer; further texturing the pyramid textured surface with the partial oxidized glass layer reserved on the spire; and removing the oxidized glass layer on the spire of the pyramid suede subjected to further texturing treatment. According to the texturing method, the controllability of the pyramid structure of the textured surface is improved, the inclination of the base angle and the side face of the pyramid structure is increased, the light trapping performance of the pyramid structure is improved, and the light utilization rate of the crystalline silicon solar cell is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a texturing method and a solar cell. Background Art

[0002] In the field of crystalline silicon solar cells, the preparation of pyramid velvet on the surface of crystalline silicon (texturing for short) has become one of the technical means to reduce light reflection. The pyramid velvet reflects and refracts light multiple times to allow more light to enter the crystalline silicon solar cell. At present, the texturing process is that alkaline solution or acid solution directly acts on the surface of the crystalline silicon substrate, and the microscopic anisotropy of crystalline silicon is used to obtain a microscopic morphology with fixed crystal planes and orderly arrangement. Compared with the planar structure, the pyramid velvet obtained by the existing texturing method can improve the utilization rate of light.

[0003] However, the existing texturing methods have limited space for adjusting the pyramid structure. For example, multiple texturing processes will corrode the entire pyramid, and its overall structure will not change much. Corrosion time is too long and may cause the top of the pyramid to be corroded, which will reduce the inclination angle of the pyramid and is not conducive to improving light utilization. Therefore, it is still necessary to explore new texturing methods to increase the adjustability of the pyramid structure in order to improve the light utilization of crystalline silicon solar cells. Summary of the invention

[0004] In view of this, the present invention provides a texturing method and a solar cell, which increases the controllability of the pyramid structure of the velvet surface, increases the bottom angle and side inclination of the pyramid structure, and increases the light trapping property of the pyramid structure, so as to improve the light utilization rate of the crystalline silicon solar cell.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0006] In a first aspect, the present invention provides a texturing method, comprising:

[0007] Step 1, preparing a pyramid velvet surface on the surface of a crystalline silicon substrate;

[0008] Step 2, forming an oxide glass layer containing a P-type doping element on the pyramid velvet surface;

[0009] Step 3, removing the portion of the oxidized glass layer corresponding to the pyramid velvet surface and the portion of the bottom of the pyramid, and retaining the portion of the oxidized glass layer corresponding to the top of the pyramid;

[0010] Step 4, further texturing the pyramid surface with a partial oxidized glass layer retained at the top of the pyramid;

[0011] Step 5: Remove the oxidized glass layer on the top of the pyramid surface that has been further textured.

[0012] In a second aspect, an embodiment of the present invention provides a solar cell, comprising: a crystalline silicon substrate, wherein the crystalline silicon substrate has a pyramid texture surface prepared by the texture making method provided by the embodiment of the first aspect above.

[0013] The technical solution of the first aspect of the above invention has the following advantages or beneficial effects:

[0014] The technical solution provided by the embodiment of the present invention first prepares a pyramid velvet surface on the surface of a crystalline silicon substrate, forms an oxide glass layer on the pyramid velvet surface, removes the portion of the oxide glass layer corresponding to the tower body and the tower bottom of the pyramid velvet surface, and retains the portion of the oxide glass layer corresponding to the tower top, and subsequently further velvets the pyramid velvet surface with a partial oxide glass layer retained on the tower top. The tower body and the tower bottom of the pyramid velvet surface can be further etched without etching the tower top, thereby increasing the bottom angle of the pyramid structure and the inclination of the side surface of the pyramid relative to the bottom surface of the pyramid. Therefore, the technical solution provided by the embodiment of the present invention can increase the controllability of the pyramid structure of the velvet surface and increase the light trapping property of the pyramid structure, so as to improve the light utilization rate of crystalline silicon solar cells. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 It is a schematic diagram of the change of the pyramid cross-section structure of the secondary velveting in the prior art;

[0016] Figure 2 It is a schematic diagram of the main process of the texturing method provided by an embodiment of the present invention;

[0017] Figure 3 It is a schematic diagram of the main steps of a primary texturing process provided by an embodiment of the present invention;

[0018] Figure 4 It is a schematic diagram of the main process of preparing the oxide glass layer of the spire provided by an embodiment of the present invention;

[0019] Figure 5 It is a schematic diagram of the main process of secondary texturing of a crystalline silicon substrate having an oxide glass layer at the top of a tower provided by an embodiment of the present invention;

[0020] Fig. 6A It is a schematic diagram of the change of the pyramid cross-sectional structure corresponding to each process of the texturing method provided by the embodiment of the present invention;

[0021] Figure 6B It is a schematic diagram of the change of the pyramid cross-section structure corresponding to the secondary texturing in the texturing method provided by the embodiment of the present invention;

[0022] Figure 7 It is a SEM picture of the velvet structure corresponding to each process of the velvet making method provided in the embodiment of the present invention.

[0023] The reference numerals are as follows:

[0024] 10-crystalline silicon substrate; 11-large pyramid; 12-small pyramid; 11'-large pyramid after secondary texturing according to the prior art; 12'-small pyramid after secondary texturing according to the prior art. DETAILED DESCRIPTION

[0025] In the field of crystalline silicon solar cells, the use of alkaline solution or acid solution to anisotropically etch different crystal planes (100 crystal plane and 111 crystal plane) of crystalline silicon to prepare orderly arranged pyramid morphology on the surface of crystalline silicon to increase the light trapping property of the crystalline silicon surface has become one of the important means to improve the light utilization rate of crystalline silicon solar cells. However, whether it is a single texturing or multiple texturing, acid solution or alkaline solution is currently used to act directly on the surface of crystalline silicon. In particular, for multiple texturing (such as secondary texturing), its purpose is mainly to modify the smaller pyramids in the velvet surface and increase the height of the smaller pyramids. However, due to multiple texturing (such as secondary texturing), the alkaline solution or acid solution will act on all the pyramids on the velvet surface simultaneously, which will not only corrode the bottom and the body of the pyramid, but also the top of the pyramid. Figure 1 As shown, after the crystalline silicon substrate 10 is subjected to a first texturing, structure A is obtained. In structure A, two pyramids of different sizes (a large pyramid 11 and a small pyramid 12) are exemplarily given. The base angles of the two large pyramids 11 and the small pyramid 12 are α1 and α2, respectively. After a second texturing, structure B is obtained. During the second texturing process, the acid solution or the alkaline solution will simultaneously corrode the base, the body and the top of the pyramid, so that the size change of the large pyramid 11 to the second-processed large pyramid 11' is not obvious, and the base angle α3 is basically the same as α1. Although the height of the small pyramid 12 to the second-processed small pyramid 12' increases to a certain extent, the base angle of the small pyramid is basically unchanged, and α4 is also basically the same as α2. Therefore, the existing multiple texturing method is mainly for small pyramids, and will not significantly change the base angle of the pyramid and the ratio of the height to the base width of the pyramid. In essence, it will not change the influence of the larger-sized pyramid on the light (that is, the path of the light on the large-sized pyramid will not change, that is, the reflectivity of the large-sized pyramid to the light will not be improved). That is to say, the existing multiple texturing methods do not significantly improve the larger-sized pyramids. The method mainly improves the light absorption of the crystalline silicon surface by increasing the height of the small-sized pyramids and reducing the difference between the large pyramids and the small pyramids. As a result, the existing multiple texturing is still not enough to make the crystalline silicon substrate fully utilize the incident sunlight, and the improvement of the light utilization rate of the crystalline silicon solar cell is not obvious. In order to improve the influence of the large-sized pyramids and the small-sized pyramids on the velvet surface on the light, the embodiment of the present invention provides a new texturing method.

[0026] in, Figure 2A schematic diagram showing the main process of the texturing method provided by an embodiment of the present invention; Fig. 6A A schematic diagram showing changes in the pyramid cross-sectional structure corresponding to the preparation method is shown; Figure 6B A schematic diagram showing the changes in the pyramid cross-section structure corresponding to secondary texturing is shown.

[0027] The embodiment of the present invention provides a texturing method. Figure 1 As shown, the texturing method may include the following steps:

[0028] Step S201: preparing a pyramid velvet surface on the surface of a crystalline silicon substrate.

[0029] The crystalline silicon substrate may be single crystal silicon or polycrystalline silicon.

[0030] Specifically, this step may include the following sub-steps:

[0031] Step S201-1: cleaning the crystalline silicon substrate; specifically, Figure 3 As shown, the crystalline silicon substrate is sequentially subjected to an ultrapure water cleaning process (SDR process) → an alkali + hydrogen peroxide mixed solution cleaning process (Psc1 process) → a process for cleaning the residual solution of the Psc1 process (R1 process). More specifically, for the SDR process, the crystalline silicon substrate is cleaned with ultrapure water at 50°C to 70°C for 1min to 10min. For the Psc1 process, the crystalline silicon substrate is cleaned at 50°C to 70°C with a solution containing 0.5% to 5% H2O2 (the 0.5% to 5% H2O2 refers to the mass fraction of H2O2 in the solution) and 0.5% to 5% KOH (the 0.5% to 5% KOH refers to the mass fraction of KOH in the solution) for 1min to 10min, wherein KOH can also be replaced by NaOH. For the R1 process, the crystalline silicon substrate is cleaned with ultrapure water (DI) at room temperature (20°C to 30°C) for 2min to 10min. The purpose of the Psc1 process is mainly to remove organic pollutants on the surface of the crystalline silicon substrate, and the purpose of the R1 process is to remove H2O2 and KOH / NaOH remaining on the silicon substrate.

[0032] The temperature of the ultrapure water used in the SDR process may be any value between 50°C and 70°C, or may fluctuate between 50°C and 70°C. For example, the temperature of the ultrapure water may be 50°C, 55°C, 60°C, 62°C, 65°C, 68°C or 70°C. In addition, the time for washing the crystalline silicon substrate with ultrapure water may be 1 min, 2 min, 5 min, 6 min, 8 min or 10 min.

[0033] For the Psc1 process, the mass fraction of H2O2 in the solution used can be 0.5%, 1%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5%, etc. In addition, the mass fraction of KOH or NaOH in the solution can be 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5%, etc. The cleaning time of the cleaning process can be 1 min, 2 min, 2.5 min, 3 min, 5 min, 6 min, 7 min, 8 min or 10 min, etc. The temperature used in the Psc1 process can be 50°C, 55°C, 60°C, 62°C, 65°C, 68°C or 70°C, etc.

[0034] For the R1 process, the cleaning time using ultrapure water (DI) can be 2 minutes, 3 minutes, 5 minutes, 6 minutes, 7 minutes, 8 minutes or 10 minutes.

[0035] Step S201-2: Using an alkaline solution to which a texturing additive is added at a mass fraction of 0.1% to 5%, the cleaned crystalline silicon substrate is treated at a temperature range of 60 to 80°C for 3 to 20 minutes to form a pyramid texturing surface on the surface of the crystalline silicon substrate, wherein the mass fraction of alkali in the alkaline solution is 0.5% to 5%.

[0036] Specifically, Figure 3 As shown, the temperature used in the texturing process (Texture1 process) of this step can be 60°C, 65°C, 68°C, 70°C, 75°C or 80°C, etc. The texturing additive (ADD) contained in the solution used in this step can directly select the existing texturing additive. The selection of the texturing additive is not repeated here. The mass fraction of the texturing additive (ADD) in the solution used in this step can be 0.1%, 0.5%, 1%, 1.2%, 1.5%, 2%, 2.3%, 2.5%, 2.8%, 3%, 3.5%, 3.8%, 4%, 4.2%, 4.5%, 4.8% or 5%, etc. In addition, the alkali used in the solution used in this step can be NaOH or KOH. The mass fraction of the alkali in the solution can be 0.5%, 1%, 1.2%, 1.5%, 2%, 2.3%, 2.5%, 2.8%, 3%, 3.5%, 3.8%, 4%, 4.2%, 4.5%, 4.8% or 5%, etc.

[0037] Furthermore, the first texture making process (Texture 1 process) may further include a process of removing the velvet residue. Figure 3As shown, the process of removing the velvet residue is more specifically, the velvet obtained in the first velvet making process is sequentially subjected to a second cleaning residual solution process (R2 process) → a third cleaning residual solution process (R3 process) → an O3 treatment process (O3 process) → an HF treatment process (HF process) → a dehydration process (HWD process).

[0038] Specifically, the R2 and R3 processes generally use ultrapure water (DI) at room temperature (20°C~30°C) to clean the crystalline silicon substrate for 1min~10min. It is worth noting that after the first texturing, Figure 3 Only two ultrapure water cleaning processes are given as examples. Depending on the needs, only one ultrapure water cleaning can be performed, or more ultrapure water cleaning can be performed. The number of ultrapure water cleanings is not limited here. The ultrapure water cleaning is mainly to remove most of the reagent residues and reaction product residues on the surface of the crystalline silicon substrate. For example, the temperature of the ultrapure water used in the R2 and R3 processes can be 20°C, 21°C, 24°C, 27°C or 30°C, etc. The cleaning time can be 1min, 2min, 4min, 5min, 7min, 8min, 9min or 10min, etc.

[0039] Further, if Figure 3 As shown, the O3 process is mainly to pass ozone into a solution containing 0.1% to 5% HCl by mass in an ozone tank, and use the HCl solution with ozone to clean the crystalline silicon substrate treated by the R3 process for 2min to 20min at room temperature. The O3 process is mainly to remove organic residues in the crystalline silicon substrate. Ultrapure water cleaning can be performed in the O3 process to remove residual solution on the surface of the crystalline silicon substrate. The mass concentration of ozone contained in the solution in this process is 30ppm to 40ppm. For example, in this process, the mass fraction of HCl in the ozone tank can be 0.1%, 0.5%, 1%, 2%, 3%, 4% or 5%. The mass concentration of ozone in the ozone tank can be 30ppm, 32ppm, 35ppm, 38ppm or 40ppm. In addition, the cleaning time of this process can be 2min, 4min, 5min, 8min, 10min, 12min, 15min, 18min or 20min.

[0040] In addition, the HF process mainly uses pickling in a 15% to 30% HF solution tank (the HF solution is mixed with 0.1% to 5% HCl by mass), the purpose of which is to remove the metal ion residues on the surface of the crystalline silicon (the metal ions are inherent in the crystalline silicon matrix, which are separated from the crystalline silicon and adhere to the surface of the crystalline silicon matrix), making the crystalline silicon surface hydrophobic, which is convenient for subsequent dehydration and drying. For example, in this process, the mass fraction of HCl can be 0.1%, 0.5%, 1%, 2%, 3%, 4% or 5%, etc. The mass fraction of HF in the HF solution tank can be 15%, 16%, 18%, 20%, 24%, 25%, 28% or 30%, etc.

[0041] Furthermore, the HWD process mainly involves washing in ultrapure water at 50°C to 70°C, dehydrating the silicon wafer using the surface tension of hot water, removing the tiny particles remaining on the surface of the silicon wafer, and finally drying to complete the texturing process to obtain product DRY1. For example, a cross-sectional schematic diagram of a pyramid on the velvet structure of product DRY1 obtained in this step can be shown as follows: Fig. 6A For example, the temperature of the ultrapure water used in this step can be 50°C, 52°C, 55°C, 60°C, 64°C, 65°C, 68°C or 70°C.

[0042] In addition, in addition to the above-mentioned chemical method for texturing, step S201 may also adopt physical methods such as plasma sputtering, laser sputtering, etc. During the texturing process using the physical method, a cleaning process is also required to remove residues.

[0043] Step S202: forming an oxide glass layer containing doped elements on the pyramid velvet surface.

[0044] The oxide glass layer containing doping elements is a film layer located on the pyramid velvet surface, and the film layer contains doping elements and silicon-oxygen structure. Fig. 6A As shown, for this step, an oxide glass layer containing P-type doping elements can be formed on the pyramid velvet surface, wherein the thickness of the oxide glass layer decreases from the top of the pyramid velvet surface to the bottom of the pyramid velvet surface.

[0045] More specifically, there are two ways to implement the step of forming an oxide glass layer containing doping elements: Implementation method 1: P-type doping elements can be diffused on the pyramid velvet surface through a diffusion process to form a diffused doping layer, and the diffused doping layer is oxidized; a mixture of P-type doping elements, silicon dioxide and residual diffusion sources, etc. forms an oxide glass layer. Implementation method 2: In this step, oxygen and silicon on the surface of the pyramid velvet surface can form a silicon dioxide layer under an oxygen atmosphere, and P-type doping elements are diffused in the silicon dioxide layer through a diffusion process, thereby obtaining an oxide glass layer containing doping elements. A mixture of P-type doping elements, silicon dioxide and residual diffusion sources, etc. forms an oxide glass layer. Among them, the parameters of the diffusion process and the oxidation process, such as the duration of the source, temperature, oxidation, etc., can be adjusted according to actual needs, and can be obtained through multiple experiments, and will not be repeated here. By first forming a silicon dioxide layer, and then diffusing the P-type doping element in the silicon dioxide layer through a diffusion process, the doping depth can be better controlled, which is conducive to the formation of a shallow junction, so that the process does not affect the performance of the solar cell prepared by the velvet surface obtained based on the velvet making method.

[0046] It is worth noting that in the above-mentioned implementation method 1 of forming the oxide glass layer containing doped elements, the oxidized diffusion doped layer can be the upper part of the oxidized diffusion doped layer, and the lower part of the diffusion doped layer is retained, that is, a diffusion doped layer and an oxide glass layer containing doped elements stacked on the diffusion doped layer are formed on the pyramid velvet surface of the crystalline silicon substrate. For the above-mentioned implementation method 2 of forming the oxide glass layer containing doped elements, part of the doping elements can also pass through the silicon dioxide layer into the pyramid velvet surface of the crystalline silicon substrate to form a doped layer. That is, in this step, in addition to forming the above-mentioned oxide glass layer containing doped elements, in the process of forming the oxide glass layer containing doped elements, the doping elements and the crystalline silicon substrate can also form an additional doping layer (or diffusion doping layer) to reduce the difficulty of process operation and the accuracy of parameter control, and improve the process operability.

[0047] In the subsequent process of removing the oxide glass layer containing doping elements, the doping layer (or diffusion doping layer) formed by the doping elements and the crystalline silicon substrate can be completely removed or partially retained. In the case where the doping layer (or diffusion doping layer) is retained, the doping layer (or diffusion doping layer) can be used as the basis for the subsequent diffusion doping to prepare the PN junction. Therefore, in the case where the doping layer (or diffusion doping layer) is retained, the doping element is selected to be the same as the doping element used for the subsequent diffusion doping to prepare the PN junction. In particular, as mentioned above, the doping element is preferably boron, and the crystalline silicon substrate is preferably an N-type silicon substrate.

[0048] Since the height of the pyramid is generally 1μm~1.5μm and the gap between the pyramids is relatively small, during the diffusion process of the P-type doping element, the diffusion distance of the tower body and the tower bottom is relatively long compared to the tower top, and the concentration of the P-type doping element gradually decreases from the tower top to the tower bottom, and there is also a certain difference in the diffusion rate and doping rate of the P-type doping element from the tower top to the tower bottom (from the tower top to the tower bottom, the diffusion rate and doping rate of the P-type doping element are reduced), making the diffusion amount of the P-type doping element in the tower body and the tower bottom smaller than that in the tower top. Therefore, the oxide glass layer formed in this step has a concentration difference and a thickness difference between the tower top position and the non-tower top position, and the formation of this concentration difference and thickness difference is the basis for the subsequent steps.

[0049] Preferably, the doping concentration of the P-type doping element contained in the oxide glass layer formed in step S202 is 1.8E18cm -3 ~1.8E21cm -3 ; For example, the doping concentration of P-type doping elements can be: 1.8E18cm -3 、1.9E18cm -3 、2.0E18cm -3 、5.0E18cm -3 、6.0E18cm -3 、7.2E18cm -3 、8.0E18cm -3 、9.0E18cm -3 、1.0E19cm -3 、2.2E19cm -3 、3.5E19cm -3 、4.0E19cm -3 、6.0E19cm -3 、8.0E19cm -3 、9.0E19cm -3 、1.0E20cm -3 、2.0E20cm -3 、2.2E20cm -3 、2.5E20cm -3 、5.5E20cm -3 、6.5E20cm -3 、7.0E20cm -3 、1.0E21cm -3 or 1.8E21cm -3Etc. It is worth noting that the doping concentration of the P-type doping element contained in the oxide glass layer generally refers to the doping concentration at the top of the pyramid. By limiting the doping concentration, on the one hand, it is possible to avoid the doping elements doped in this step from affecting the performance of the subsequently prepared solar cell; on the other hand, the subsequent step S203 can be completed relatively easily, providing a relatively loose operating time for the subsequent step S203, reducing the accuracy, difficulty and complexity of the texturing process provided in the embodiment of the present application, so as to effectively improve the product yield.

[0050] Further preferably, the thickness of the oxide glass layer formed in this step is generally 100nm~150nm; for example, the thickness of the oxide glass layer may be 100nm, 110nm, 120nm, 125nm, 128nm, 130nm, 133nm, 135nm, 140nm, 145nm, 148nm or 150nm, etc. It is worth noting that the thickness of the oxide glass layer generally refers to the thickness of the oxide glass layer in the pyramid top area. By limiting the thickness of the oxide glass layer, a more relaxed time available for operation can be further provided for the subsequent step S203, and the accuracy, difficulty and complexity of the texturing process provided in the embodiment of the present application can be further reduced, so as to further effectively improve the yield rate of the product.

[0051] The above-mentioned P-type doping element is generally selected as boron. In the process of doping the boron element into silicon, it is significantly affected by the pyramid. From the top of the pyramid to the body and the bottom of the pyramid, the diffusion distance of the boron element increases significantly. Compared with the middle or body of the pyramid, the top of the pyramid will accumulate more boron atoms, so that the boron element doping in the pyramid from the top of the pyramid to the body and the bottom of the pyramid will produce a significant thickness difference and concentration difference (that is, the thickness and concentration of the oxide glass layer containing the doping element corresponding to the top of the pyramid are greater than those of the body of the pyramid, and the thickness and concentration of the oxide glass layer containing the doping element corresponding to the body of the pyramid are greater than those of the bottom of the pyramid). Similarly, during the oxidation process, the top of the tower is always in a high-concentration O2 atmosphere. After the initial O2 is exhausted in the bottom part of the tower, O2 needs to diffuse from a farther position to replenish it. Therefore, the mask layer at the top of the tower is usually thicker and has a higher concentration. Therefore, different chemical corrosion windows are produced at the top of the tower, the middle of the tower, and the bottom of the tower. And in the subsequent process of selecting hydrofluoric acid (HF) to remove the doped boron element, the reaction of HF and boron element has a certain buffer reaction rate, so that there is a time window available for operation for removing the oxide glass layer at the bottom of the pyramid, the oxide glass layer at the tower body and the oxide glass layer at the top of the pyramid, that is, the reaction rate of removing the oxide glass layer in a specific concentration of HF solution between the bottom and the tower body of the pyramid is quite different from that of the top of the pyramid. This relatively wide reaction window can better complete the following step S203, further provide a more relaxed time available for operation for the subsequent step S203, and further reduce the operating accuracy, difficulty and complexity of the texturing process provided in the embodiment of the present application, so as to further effectively improve the product yield.

[0052] In addition, this step further includes: in the case of forming a diffuse doping layer, controlling the diffusion depth of the doping element to be 0.8 μm to 1.1 μm. For example, the diffusion depth of the doping element may be 0.8 μm, 0.9 μm, 1.0 μm or 1.1 μm. The diffusion depth of the doping element refers to the depth of diffusion from the surface of the oxide glass layer to the crystalline silicon substrate.

[0053] The depth of the doped diffusion element is controlled by the source flow, oxidation temperature and oxidation time of the diffusion process. Controlling the doping depth within this range can ensure the completion of the technical solution and reduce the probability of Auger recombination between the doping element and the matrix. The temperature can be set to 800°C~1100°C, the source flow time is 3min~30min, and the source flow is 100sccm~200sccm; preferably, for BCl3 as the B doping source, the doping temperature can be 800℃~900℃, the source flow time is 3min~10min, and the source flow is 120sccm~150sccm, so that the diffusion depth of the doping element is 0.8μm~1.1μm. The diffusion depth of the doping element is to provide sufficient reaction window to better meet the need to retain the part of the oxide glass layer corresponding to the top of the tower.

[0054] The cross section of the pyramid with the oxide glass layer obtained after the processing in step S202 is as follows Fig. 6A As shown, the oxide glass layer gradually thickens from the bottom of the tower to the top of the tower.

[0055] It is worth noting that the oxide glass layer containing doped elements provided in the above embodiment of the present invention is only a preferred method. In this step, other masks can also be used to replace the oxide glass layer containing doped elements.

[0056] Step S203: removing the portion of the oxidized glass layer corresponding to the pyramid velvet surface, which corresponds to the pyramid body and the bottom, and retaining the portion of the oxidized glass layer corresponding to the pyramid tip.

[0057] Specifically, the step can use an acid solution to clean the oxide glass layer; as mentioned above, since the thickness of the oxide glass layer containing doping elements formed in the above step S202 decreases from the top of the tower to the bottom of the tower, the time required for the acid solution to clean the oxide glass layer with different thicknesses is different, that is, in the process of using the acid solution to simultaneously clean the top of the tower, the tower body and the bottom of the tower, the oxide glass layer containing doping elements at the bottom of the tower and the tower body is smaller in thickness and is first completely cleaned by the acid solution. After the oxide glass layer containing doping elements at the bottom of the tower and the tower body is completely cleaned by the acid solution, since the oxide glass layer containing doping elements corresponding to the top of the tower is thicker, only part of it is cleaned and removed by the acid solution, and the top of the tower will still retain the oxide glass layer containing doping elements (the retained oxide glass layer containing doping elements is the part that has not been removed by the acid solution due to the cleaning time limit). That is to say, with respect to the technical means of using an acid solution to clean the oxide glass layer, the part of the oxide glass layer corresponding to the top of the tower retained in this step is essentially the part that has not been removed at the top of the tower after the tower body and the bottom of the tower are completely removed by the acid solution. In particular, as mentioned above, for the acid solution cleaning of the oxide glass layer, the above doping element is preferably boron, which allows a relatively wide acid solution cleaning time window between the tower body, the tower bottom and the tower top, facilitates process implementation, and has relatively low requirements on process operation accuracy and complexity. Figure 4 As shown, the acid treatment process (HF" process) can use a 20% to 30% HF solution for cleaning for 100s to 400s. For example, the mass fraction of HF in the solution can be 20%, 22%, 24%, 26%, 28% or 30%, and the cleaning time can be 100s, 150s, 180s, 200s, 240s, 260s, 300s, 320s, 350s, 380s or 400s. In addition, this step can also use physical etching methods such as laser etching to remove the tower body and the bottom of the tower corresponding to the pyramid velvet surface, and retain the part of the oxide glass layer corresponding to the top of the tower. After this step, a product DRY2 with a silicon oxide glass layer retaining the top of the tower can be obtained. The cross-section of the pyramid in DRY2 is shown as follows. Fig. 6A shown.

[0058] Furthermore, after this step, Fig. 6A As shown, the height D of the portion corresponding to the top of the tower retained in the oxide glass layer is 50nm~60nm. The height D is essentially the length of the side of the oxide glass layer. By controlling the height D of the portion corresponding to the top of the tower retained in the oxide glass layer, it is helpful to control the size of the base angle of the pyramid formed by the subsequent secondary texturing.

[0059] Step S204: further texturing the pyramid surface with a portion of the oxidized glass layer retained at the top of the pyramid.

[0060] Specifically, Figure 5 As shown, the secondary texturing process (Texture2 process) is generally carried out at 60°C~80°C, using an alkaline solution (the mass fraction of alkali in the alkaline solution is 0.1%~0.5%) to treat the pyramid velvet surface with a partial oxidized glass layer retained at the top of the tower for 500s~700s with a texturing additive (ADD) of 0.1%~3% by mass. The texturing additive used in this step can be the same as the texturing additive used in the texturing process of step S201 above, or it can be different, and no limitation is made here. The mass fraction of the texturing additive in the solution of this step can be 0.1%, 0.5%, 1%, 1.2%, 1.5%, 2%, 2.3%, 2.5%, 2.8%, 3%, etc. The alkaline solution can be a KOH solution or a NaOH solution. The mass fraction of the alkali in the alkaline solution used in this step can be 0.1%, 0.2%, 0.3%, 0.4% or 0.5%, etc. A low-concentration alkaline solution is used for the secondary texturing. It is worth noting that the concentration of the alkaline solution used in the secondary texturing is lower than the concentration of the alkaline solution used in the texturing process of step S201. That is to say, when the concentration of the alkaline solution used in the texturing process of step S201 is 0.5%, the concentration of the alkaline solution used in step S204 is lower than 0.5%.

[0061] In this step, by using a lower concentration of alkaline solution for secondary texturing, it can ensure that the alkaline solution will not damage the pyramid tip protected by the oxide glass layer while further corroding the tower body and the tower bottom. Fig. 6A As shown in FIG. 1 , compared with the pyramid with one-time texturing, the second texturing after this step can extend the height of the bottom of the pyramid by ΔH), while the position of the top of the pyramid can remain unchanged, so as to change the bottom angle of the pyramid from α5 to α6. Fig. 6A As shown in the figure, α6 is greater than α5. Generally speaking, after the first texturing process, the α5 is about 55°, and after the second texturing process, the α6 is 60°~70°. For example, α6 can be 60°, 62°, 64°, 65°, 67°, 69° or 70°. More specifically, the structural changes brought about by the second texturing process (Texture2 process) are as follows: Figure 6BAs shown. In the secondary texturing process, the action of the alkaline solution is mainly divided into two stages. The first stage of the action of the alkaline solution: in the secondary texturing process using a lower concentration of alkaline solution, the space of the pyramid body and the bottom area is limited, and the alkaline solution it can accommodate is relatively limited. The alkali in this part of the alkaline solution will be quickly exhausted. The alkali in the alkaline solution in other areas (the other areas are the areas from the tower body and the bottom area to the outside) will move to the tower body and the bottom of the tower by diffusion. On the tower body, the closer to the top of the tower, the earlier it contacts with the diffused alkali, and the closer to the bottom of the tower, the later it contacts with the diffused alkali, that is, from the position close to the top of the tower to the direction away from the top of the tower, until the bottom of the tower, the action time of the diffused alkali gradually decreases. Therefore, in the secondary texturing process, from the position close to the top of the tower to the bottom of the tower, the corrosion of the tower body by the alkaline solution gradually weakens. However, due to the presence of the oxide glass layer containing doped elements, the top of the tower will not be corroded. Figure 6B It can be seen that when the alkaline solution starts to act, the tower body is corroded first, and because the time of the diffused alkali action gradually becomes shorter from the position close to the top of the tower to the bottom of the tower, the corrosion of the alkaline solution is gradually weakened accordingly. This process makes the base angle of the pyramid smaller (that is, smaller than the base angle α5 of the pyramid before the secondary texturing). Further, as the secondary texturing time increases, the action of the alkaline solution enters the second stage. In this second stage, after the alkali in the alkaline solution diffuses to the bottom of the pyramid, as the action time of the alkaline solution increases, the top of the tower will still not be corroded by the alkaline solution under the protection of the oxide glass layer containing doped elements. The corrosion arc of the alkaline solution on the bottom and the tower body moves down, making the pyramid higher and higher. The pyramid heightening process will increase the inclination of the tower body, thereby increasing the base angle from α5 to α6 (α6 is greater than α5).

[0062] Further, if Figure 5 As shown, before this step, it may include: alkaline solution cleaning process (Psc2 process) → ultrapure water cleaning process (R1'). Specifically, for the Psc2 process, a solution containing 0.5%~5% H2O2 by mass and 0.5%~5% KOH by mass is used to clean the crystalline silicon substrate at 50℃~70℃ for 1min~10min, wherein KOH can also be replaced by NaOH. The purpose of the Psc2 process is mainly to remove velvet residues. For the R1' process, the crystalline silicon substrate is cleaned with ultrapure water at 50℃~70℃ for 2min~10min. Among them, the purpose of the R1' process is to remove the H2O2 and KOH / NaOH remaining on the silicon substrate.

[0063] For the Psc2 process, the mass fraction of H2O2 in the solution used can be 0.5%, 1%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5%, etc. In addition, the mass fraction of KOH or NaOH in the solution can be 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5%, etc. The cleaning time of the cleaning process can be 1 min, 2 min, 2.5 min, 3 min, 5 min, 6 min, 7 min, 8 min or 10 min, etc. The temperature used in the Psc2 process can be 50°C, 55°C, 60°C, 62°C, 65°C, 68°C or 70°C, etc.

[0064] For the R1' process, the cleaning time using ultrapure water at room temperature can be 2 min, 3 min, 5 min, 6 min, 7 min, 8 min or 10 min.

[0065] In addition, if Figure 5 As shown, after the above-mentioned secondary texturing process (Texture2 process), the following treatment processes may be further included: ultrapure water cleaning process (R2' process) → O3 treatment process (O3 process).

[0066] Specifically, the R2' process generally uses room temperature ultrapure water to clean the crystalline silicon substrate for 1min~10min. It is worth noting that after the secondary texturing, Figure 5 Only one ultrapure water cleaning process is given as an example. Multiple ultrapure water cleanings can be performed as needed, and the number of ultrapure water cleanings is not limited here. The ultrapure water cleaning is mainly to remove most of the reagent residues and reaction product residues on the surface of the crystalline silicon substrate. For example, the cleaning time of the R2' process can be 1 min, 2 min, 4 min, 5 min, 7 min, 8 min, 9 min or 10 min, etc.

[0067] Further, if Figure 5As shown, the O3 process is mainly to pass ozone through a 0.1% to 5% HCl solution in an ozone tank, and use the HCl solution containing ozone to clean the substrate treated by the R2' process at room temperature for 2min to 20min. The O3 process is mainly to remove organic residues from the crystalline silicon substrate. Ultrapure water cleaning can be performed in the O3 process to remove residual solution on the surface of the crystalline silicon substrate. The mass concentration of ozone in this process can be 30ppm to 40ppm. For example, in this process, the mass fraction of HCl in the ozone tank can be 0.1%, 0.5%, 1%, 2%, 3%, 4% or 5%. The mass concentration of ozone in the ozone tank can be 30ppm, 32ppm, 35ppm, 38ppm or 40ppm. In addition, the cleaning time of this process can be 2min, 4min, 5min, 8min, 10min, 12min, 15min, 18min or 20min.

[0068] The ultrapure water cleaning process after the secondary texturing (R2' process) → O3 treatment process (O3 process) can be directly completed using the second cleaning residual solution process after the primary texturing (R2 process) → the third cleaning residual solution process (R3 process) → O3 treatment process (O3 process), so as to reduce the equipment used for texturing treatment, reduce parameter control, improve production efficiency, and facilitate industrialization.

[0069] In addition, in this step, secondary texturing is carried out in a low concentration of alkali, which causes the base of the pyramid to move downward, thereby increasing the height of the pyramid in disguise. The pyramid becomes taller and "steeper", greatly increasing the secondary and tertiary reflections of light between the pyramids, significantly improving the light trapping effect of the velvet surface, and greatly reducing the reflectivity.

[0070] Step S205: removing the oxide glass layer on the top of the pyramid surface that has been further textured.

[0071] Specifically, Figure 5 As shown, this step performs an HF treatment process (HF' process). This step uses a hydrofluoric acid (HF) solution with a mass fraction of 20% to 35% (the HF solution is mixed with 1% to 5% HCl) for cleaning for 200 to 400 seconds. The HF mass fraction and HCl mass fraction used in the HF' process are higher than the HF mass fraction and HCl mass fraction used in the first post-texturing HF process.

[0072] The HF' process mainly uses a HF solution with a mass fraction of 20% to 35% (the HF solution is mixed with HCl with a mass fraction of 1% to 5%) for pickling, the purpose of which is to remove the oxide glass layer on the top of the tower and make the crystalline silicon surface hydrophobic, which is convenient for subsequent dehydration and drying. For example, in this process, the mass fraction of HCl in the solution can be 1%, 2%, 3%, 4% or 5%. The mass fraction of HF in the HF solution can be 20%, 23%, 25%, 26%, 28%, 30%, 34% or 35%. The mass fraction of HF and the mass fraction of HCl in the solution used in this step are higher than the HF and HCl used in the first post-texturing HF process. Specifically, when the mass fraction of HF used in this step is 20%, the mass fraction of HF used in the first post-texturing HF process is less than 20%; when the mass fraction of HF used in this step is 25%, the mass fraction of HF used in the first post-texturing HF process is less than 25%, etc. When the mass fraction of HCl used in this step is 1%, the mass fraction of HCl used in the first post-texturing HF process is less than 1%, etc.

[0073] Further, if Figure 5 As shown in FIG. 1 , after the HF' process, a dehydration process (HWD' process) may be further included. The HWD' process mainly involves washing in ultrapure water at 50°C to 70°C, using the surface tension of hot water to dehydrate the silicon wafer, removing the tiny particles remaining on the surface of the silicon wafer, and finally drying to complete the texturing process. The pyramid cross-section of the product DRY3 is shown in FIG. Fig. 6A For example, the temperature of the ultrapure water used in this step can be 50°C, 52°C, 55°C, 60°C, 64°C, 65°C, 68°C or 70°C.

[0074] It is worth noting that the solutions involved in the embodiments of the present invention (such as solutions containing HF, solutions containing alkali such as KOH or NaOH) are generally prepared using ultrapure water. The ultrapure water (DI) used in the technical solutions provided in the embodiments of the present invention generally refers to industrial ultrapure water.

[0075] In summary, although the technical solution provided by the embodiment of the present invention also undergoes two texturing processes, due to the introduction of an oxide glass layer containing doped elements formed on the pyramid velvet surface and the removal of the portion of the oxide glass layer corresponding to the pyramid body and the bottom of the pyramid velvet surface, and the retention of the portion of the oxide glass layer corresponding to the top of the pyramid, the second texturing process only processes the pyramid body and the bottom of the pyramid without affecting the top of the pyramid, allowing the pyramid to continue to grow, and all the pyramids as a whole "grow taller", effectively increasing the aspect ratio of the pyramid (the ratio between the height of the pyramid and the width of the bottom of the pyramid) and the base angle height.

[0076] In addition, in the above process, a structure of a boron-containing silicon oxide glass layer is formed by doping with boron elements, and a boron-doped oxide glass layer (BSG) containing the element is formed on the surface of the crystalline silicon substrate, the thickness of which decreases from the top of the pyramid velvet surface to the bottom of the pyramid velvet surface. The existence of the BSG can slow down the reaction rate of the oxide glass layer and the acid solution, so that the time required for the acid solution to clean BSG of different thicknesses and doping concentrations is quite different. The thickness of the BSG decreases from the top of the pyramid velvet surface to the bottom of the pyramid velvet surface, which provides a sufficient time reaction window for retaining the BSG at the top of the pyramid (i.e., it takes a relatively long time to clean all the BSG at the top of the pyramid velvet surface). Using this time reaction window, BSG can be cleaned with an acid solution to remove the parts of the BSG corresponding to the pyramid body and bottom, and retain the part of the BSG corresponding to the top of the pyramid. The pyramid top of the pyramid with part of BSG retained can be further textured to further etch the body and bottom of the pyramid top without etching the top of the pyramid. Based on this, the controllability of the pyramid structure of the velvet can be increased, the bottom angle of the pyramid structure and the inclination of the pyramid side relative to the bottom of the pyramid can be increased, the secondary and tertiary reflections of light between the pyramids can be greatly increased, the light trapping effect of the velvet is significantly improved, and the reflectivity is greatly reduced, so as to improve the light utilization rate of crystalline silicon solar cells.

[0077] Furthermore, an embodiment of the present invention provides a solar cell. The solar cell may include: a crystalline silicon substrate, wherein the crystalline silicon substrate has a pyramid texture surface prepared by the texture making method provided by the above embodiment.

[0078] Among them, Fig. 6A As shown in FIG. 1 , the top of the pyramid velvet surface is a cap structure. Specifically, as Fig. 6A As shown, the extension line of the side of the tower body to the top of the tower spire is located on the inner side of the tower spire, making the tower spire look like a "cap" covering the top of the pyramid velvet surface. Specifically, the cap structure is formed by the velvet making method provided by the above embodiment. More specifically, as Fig. 6A As shown, during the texturing process, the pyramid velvet structure is covered by the oxide glass layer containing doped elements. Due to the characteristics of the pyramid velvet structure, the thickness of the oxide glass layer containing doped elements formed on the bottom and body of the tower is less than the thickness of the oxide glass layer containing doped elements at the top of the tower. Then, during the process of removing the oxide glass layer containing doped elements by HF solution, the oxide glass layer containing doped elements on the bottom and body of the tower is completely removed, and the oxide glass layer containing doped elements at the top of the tower will remain. In the subsequent secondary texturing process, the bottom and body of the tower will be further corroded, while the top of the tower will not be corroded due to the protection of the oxide glass layer containing doped elements. The retained top of the tower makes the top of the tower look like a "hat" covering the top of the pyramid velvet.

[0079] Furthermore, the base angle of the pyramid velvet surface is 60°~70°, for example, it can be 60°, 62°, 63°, 65°, 67°, 69° or 70°.

[0080] Compared with the existing solar cells, the solar cell provided by the present invention has a larger base angle of the pyramid velvet surface of the crystalline silicon substrate, which greatly increases the secondary and tertiary reflections of light between the pyramids, significantly improves the light trapping effect of the velvet surface, and greatly reduces the reflectivity, thereby improving the light utilization rate of the crystalline silicon solar cell.

[0081] The texturing method provided by the embodiment of the present invention is described in detail below with a specific embodiment.

[0082] Example 1

[0083] Step A: Select an N-type silicon substrate and wash the N-type silicon substrate with 60° C. ultrapure water for 2 minutes;

[0084] Step B: Clean the N-type silicon substrate at 60°C with a solution of 2% H2O2 and 2% KOH by mass for 2 minutes;

[0085] Step C: Clean the N-type silicon substrate using 25°C ultrapure water;

[0086] Step D: using an alkaline solution containing 3% alkali by mass and added with 0.2% of a texturing additive (the texturing additive used in this step is a texturing additive of model FL-06K purchased from Jingbao Company), the N-type silicon substrate is treated at 80° C. for 5 minutes to obtain a velvet-surfaced N-type silicon substrate;

[0087] Step E: washing the suede N-type silicon substrate multiple times with 25° C. ultrapure water;

[0088] Step F: Cleaning the velvet N-type silicon substrate in an ozone bath containing 2% HCl and 35 ppm O3 at room temperature for 3 minutes;

[0089] Step G: using an HF solution bath containing 15% by mass HF (the HF solution is mixed with 3% by mass HCl) to pickle the velvet N-type silicon substrate;

[0090] Step H: washing the suede N-type silicon substrate in ultrapure water at 70° C.;

[0091] The above process is a one-time velvet process, and the SEM image of the velvet surface obtained is as follows: Figure 7 (a) and Figure 7 (c). Figure 7 As shown in (a), after the first pile-making process, the sizes of the pyramid pile surfaces obtained vary greatly.

[0092] Step I: Forming a boron-containing element concentration of 1.9E19cm on the pyramid velvet surface in the velvet N-type silicon substrate -3 Oxide glass layer;

[0093] Step J: using a 20% by mass HF solution to clean the N-type silicon substrate on which the oxidized glass layer was formed for 200 seconds to form a pyramid velvet surface with a portion of the oxidized glass layer retained at the top;

[0094] Step K: using a solution containing 2% by mass H2O2 and 2% by mass KOH to clean the pyramid velvet surface with a partially oxidized glass layer at the top of the pyramid for 2 minutes at 70°C;

[0095] Step L: further washing the pyramid velvet surface with a partially oxidized glass layer retained at the top of the tower with ultrapure water at 70°C;

[0096] The scanning electron microscope image of the velvet surface obtained in this step is as follows Figure 7 (b) shown.

[0097] Step M: treating the pyramid velvet surface with a partial oxidized glass layer retained on the top of the tower with a KOH solution containing 0.3% alkali by mass and added with a 2% by mass texturing additive (the texturing additive selected in this step is a texturing additive with a model number of FL-06K produced by Jingbao Company) at 80° C. for 660 seconds to obtain a secondary texturing product;

[0098] Step N: further washing the secondary texturing product with ultrapure water at 30°C;

[0099] Step O: cleaning in an ozone tank containing 3% HCl and 38 ppm O3 at room temperature for 5 min;

[0100] Step P: washing the secondary texturing product with a 35% by mass HF solution to remove the oxide glass layer at the top of the tower to obtain the target silicon substrate;

[0101] Step Q: The target silicon substrate is further cleaned using ultrapure water at 70°C.

[0102] The scanning electron microscope image of the velvet surface obtained by the above process is as follows Figure 7 (d) shown.

[0103] contrast Figure 7 (c) and Figure 7 (d) It can be clearly seen that the bottom angle α6 of the pyramid structure prepared by the solution provided by the embodiment of the present invention is significantly larger than the bottom angle α5 of the pyramid structure obtained by one-time texturing.

[0104] Comparative example: Compared with the above embodiment, steps I to L and step P are omitted.

[0105] By conducting a light reflection test on the crystalline silicon substrate obtained in the above-mentioned Example 1 and the crystalline silicon substrate obtained in the comparative example under the same conditions, the velvet reflectivity of the crystalline silicon substrate in the comparative example is about 10.2%; the reflectivity of the velvet of the crystalline silicon substrate prepared in Example 1 is about 8.2%. It can be seen that compared with the comparative example, the scheme provided in Example 1 reduces the reflectivity of the velvet of the crystalline silicon substrate by 19.6%, and the reflectivity of the velvet prepared in this Example 1 is reduced to less than 9%, which is a very significant reduction. Among them, the reduction rate of the reflectivity of the velvet of the crystalline silicon substrate is obtained by the following calculation formula:

[0106] Rate of change of reflectivity =

[0107] The introduction provided in the above steps is only used to help understand the method, structure and core idea of ​​the present invention. For ordinary technicians in this technical field, without departing from the principle of the present invention, several improvements and modifications can be made to the present invention, and these improvements and modifications also belong to the scope of protection of the claims of the present invention.

Claims

1. A texturing method, characterized in that: include: Step 1, preparing a pyramid velvet surface on the surface of a crystalline silicon substrate; Step 2, forming an oxide glass layer containing doping elements on the pyramid velvet surface; Step 3, removing the portion of the oxidized glass layer corresponding to the pyramid velvet surface and the portion of the bottom of the pyramid, and retaining the portion of the oxidized glass layer corresponding to the top of the pyramid; Step 4, further texturing the pyramid surface with a partial oxidized glass layer retained at the top of the pyramid; Step 5: Remove the oxidized glass layer on the top of the pyramid surface after further texturing.

2. The texturing method according to claim 1, characterized in that: Step 1 includes: Step 11, cleaning the crystalline silicon substrate; Step 12: Use an alkaline solution added with a texturing additive with a mass fraction of 0.1% to 5% to treat the cleaned crystalline silicon substrate at a temperature range of 60 to 80° C. for 3 to 20 minutes to form a pyramid texturing surface on the surface of the crystalline silicon substrate, wherein the mass fraction of the alkali in the alkaline solution is 0.5% to 5%.

3. The texturing method according to claim 1, characterized in that: Step 2 comprises: forming an oxide glass layer containing a P-type doping element on the pyramid velvet surface, wherein the thickness of the oxide glass layer decreases from the top of the pyramid velvet surface to the bottom of the pyramid velvet surface; Preferably, the doping concentration of the P-type doping element contained in the oxide glass layer formed in step 2 is 1.8E18cm -3 ~1.8E21cm -3 ; Preferably, the thickness of the oxide glass layer formed in step 2 is 100 nm to 150 nm; Preferably, the P-type doping element is boron.

4. The texturing method according to claim 3, characterized in that: Step 2 includes: Diffusion of P-type doping elements on the pyramid velvet surface by a diffusion process to form a diffusion doping layer, and oxidation of the diffusion doping layer; or, In an oxygen atmosphere, a silicon dioxide layer is formed on the surface of the pyramid velvet surface, and a P-type doping element is diffused in the silicon dioxide layer through a diffusion process.

5. The texturing method according to claim 4, characterized in that: Step 2 also includes: in the case of forming the diffusion doping layer, controlling the diffusion depth of the doping element to be between 0.8 μm and 1.1 μm.

6. The texturing method according to claim 1 or 3, characterized in that: Step 3 includes: cleaning the oxide glass layer with an acid solution; Preferably, step 3 comprises: cleaning with a hydrofluoric acid solution having a mass fraction of 20% to 30% for 100s to 400s.

7. The texturing method according to any one of claims 1 to 5, characterized in that: Step 4 comprises: treating the pyramid velvet surface with a partial oxidized glass layer retained at the top of the pyramid for 500s to 700s at 60° C. to 80° C. using an alkaline solution to which a velvet-making additive with a mass fraction of 0.1% to 3% is added, wherein the mass fraction of the alkali in the alkaline solution is 0.1% to 0.5%; and / or, Step 5 includes: cleaning with a hydrofluoric acid solution having a mass fraction of 20% to 35% for 200s to 400s; and / or, In step 3, the height of the portion of the oxide glass layer corresponding to the tower tip retained is 50 nm to 60 nm.

8. A solar cell, characterized in that: include: A crystalline silicon substrate, wherein the crystalline silicon substrate has a pyramid texture surface prepared by the texture making method according to any one of claims 1 to 7.

9. The solar cell according to claim 8, characterized in that The top of the pyramid velvet surface is a cap structure.

10. The solar cell according to claim 8 or 9, characterized in that: The base angle of the pyramid velvet surface is 60° to 70°.